THE ENGLISH TEACHERS’ PERCEPTIONS AND PROBLEMS IN IMPLEMENTING CURRICULUM 2013 IN SENIOR HIGH SCHOOL - Nurlisa Nurlisa; Clarry Sada; Ikhsanudin Ikhsanudin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2018)
Teachers’ perception toward the implementation of the new curriculum is one of the fascinating topics to discuss. This research explored the teachers’ perception and problems in the implementing of curriculum 2013 in two senior high schools. It was conducted in qualitative research and the technique of collecting the data by was the interview. The participants of this study were two English teachers who taught at different senior high schools in Sambas. The data analysis was from teachers’ statements and answer. This research focused on the teachers’ perception and problem based on some indicators, namely teachers’ knowledge, teachers’ emotion, teachers’ behavior, and teacher’s motivation. The result of this research showed that teachers had good perception toward implementing curriculum from their understanding on curriculum 2013. Furthermore, this study showed some problems such as applying the scientific approach, the students’ capability, and time allocation.